Response of Pongamia Pinnata Seedlings to Root and Shoot Manipulation Techniques - Garg, Rakesh Kumar (Indian Forester, 2014)
The aim of the present investigation was to evaluate the effect of root trimming, shoot topping, pre-sowing seed soaking treatments and seed/ pod weight on seedling quality and early growth in Pongamia pinnata. Root coiling was reduced when roots were trimmed at 5 cm length. Maximum number of nodules was observed in plants with trimmed roots as compared to untrimmed. Shoot topping at 10 cm height resulted in maximum shoot and root growth. In trial on effect of seed/pod weight on seed germination, maximum seed germination was achieved in seeds with minimum 100- seed weight among the different treatments tried. Among the pre-sowing seed treatments, maximum seed germination was observed with 8 hours of water soaking. Maximum height and diameter was observed in seeds with no water soaking treatments.